The Influence of Livelihood on the Income of the Niopanda Village Community - Nur Cahya Ninsih; M. Syahrun; Susi Susanti Adang; Alitalia Indah Sari; Sitti Umama (Journal of English Language and Education, 2026)
Livelihood is a key pillar in determining the level of economic welfare of rural communities. This study aims to analyze the influence of livelihood types on the income levels of residents of Niopanda Village, Kota Baru District, Ende Regency. The focus of the study was directed at residents who work as farmers with a total of 30 respondents. The research method used is a descriptive quantitative method with data collection techniques through questionnaires and interviews, using independent variables (types of livelihood commodities) and dependent variables (income levels) which were analyzed using descriptive statistics in the form of frequency distributions. The results of the study indicate that the type of livelihood as a farmer is still the dominant sector in the residents' economy, although the income obtained tends to fluctuate and depends on the planting season and market conditions. Quantitatively, it was found that 40% of farmers earn less than Rp1,500,000, 60% rely on cashew commodities with seasonal incomes of Rp500,000–Rp1,000,000, and 40% rely on candlenuts with stable incomes of Rp1,000,000–Rp1,500,000 per month. This study concludes that diversification of agricultural commodities significantly affects the stability of rural community income.